Evaluation of different safety-engineered protection mechanisms of port access needles using a lifelike model of vascular access routes - Gabler, Feline; Heiden, Pierre; Deibert, Peter; Steinmann, Daniel (Frontiers in Medical Technology, 2025)
BackgroundPreventing needlestick injuries caused by hypodermic needles is crucial for healthcare personnel. In this context, port access needles play an important role. However, systematic comparisons of different safety-engineered port access needles have not been conducted. Therefore, we evaluated differences in product characteristics and user preferences of safety-engineered protection mechanisms of port access needles.MethodsPort puncture was performed using port access needles with four different safety mechanisms: (a) EZ Huber™ PFM Medical, (b) Gripstick® Safety OMT, (c) Gripper Micro® Smiths Medical and (d) pps ct® Vygon. Each needle type was used in three consecutive tries: an uninstructed first handling, after which instructions were given according to operating manual. Subsequently, a first and second trial were conducted. Study endpoints included successful activation, activation time, way of activation (one hand or two hands), correct activation, possible risk of needlestick injury, possibility of deactivation and preferred safety mechanism.ResultsOverall, successful activation rate during the second trial was equal for all four devices (100%). Median activation time was (a) 6 s, (b) 3 s, (c) 11 s and (d) 6 s. Single-handed activation during the second trial was (a) 0%, (b) 75%, (c) 1% and (d) 1%. Single-handed activation after further preparation with two hands during the second trial was (a) 0%, (b) 0%, (c) 0% and (d) 50%. Correct activation during the second trial was (a) 97%, (b) 66%, (c) 19% and (d) 44%. Possible risk of needlestick injury during the second trial was highest with (b). Possibility of deactivation was (a) 75%, (b) 94%, (c) 97% and (d) 22%. Individual preferences for each system were (a) n = 5, (b) n = 2, (c) n = 1 and (d) n = 24. The main written reasons given for preference were the safety protection mechanism and handling of the port needle.ConclusionWe have shown significant differences regarding product characteristics of safety mechanisms of port access needles. Our evaluation approach provides specific data for both, technical (e.g., single-handed activation) and personal device selection criteria (e.g., preference of the safety mechanism).